Qwen3 Performance on Mathematical Reasoning Benchmarks vs. State-of-the-Art LLMs - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: How does Qwen3's performance on mathematical reasoning benchmarks (e.g., GSM8K, MATH) compare to other state-of-the-art LLMs like GPT-4 and Claude 3 in terms of accuracy and scaling with model size. 13 claims were extracted from source literature; 13 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.7/10. This report
Machine-generated literature synthesis.